Answer:
The circle equation that has center , (1,-3) and passes through , (-6,-2) is given as
![(x-1)^2 + (y+3)^2 = 50](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3agzv9lf64jhwxebsmv4m99n5628mr0iil.png)
Explanation:
Here, the coordinate (h,k) of the center of circle = (1,-3)
Also, the point (x,y) on the circle = (-6,-2)
Let us assume the radius of the circle = r
The General equation of Circle is :
![(x-h)^2 + (y-k)^2 = (r)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ty01itmcq5dmzihfr0kx5188dpjdfgrp1s.png)
Substituting the value of (h,k) and (x,y) , we get:
![(-6-1)^2 + (-2-(-3))^2 = r^2\\\implies (-7)^2 + (-1)^2 = r^2\\\implies 49 + 1 = r^2\\\implies r= √(50) = 7.07](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yek87jl2hqq9yfue7i0x337p9pkdutsxyc.png)
So, the radius of the circle = 7.07 units
Now, substitute the value of (h,k) = (1,-3) and r = 7.07 back in to the general circle equation, we get:
![(x-1)^2 + (y-(-3))^2 = (7.07)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/odkq7s63ex5er6pgp0356rmrij2q9r8anu.png)
![\implies (x-1)^2 + (y+3)^2 = 50](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d29hsbb96pe8eljqftk27dghxyiruzayyt.png)
Hence, the circle equation that has center , (1,-3) and passes through , (-6,-2) is given as
![(x-1)^2 + (y+3)^2 = 50](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3agzv9lf64jhwxebsmv4m99n5628mr0iil.png)